A tool for evaluating the archaeological heritage vulnerability to coastal processes: The case study of Naples Gulf (southern Italy). (1st September 2019) - Mattei, G.; Rizzo, A.; Anfuso, G.; Aucelli, P.P.C.; Gracia, F.J.
Abstract: This paper presents a methodological approach for the determination of the vulnerability of coastal archaeological sites to marine and aeolian processes, e.g. wave erosion, temporary flooding, wind erosion, etc. The methodology allows defining different degree of vulnerability, taking into account both the potential impacts of the physical processes and the architectural characteristics of the investigated archaeological structures. The method is based on the application of specific vulnerability matrices, accurately defined for each coastal zone (i.e. the backshore, foreshore, nearshore and offshore) where archaeological sites are actually located. Results allow identifying the vulnerability level of each specific site and the index therefore represents an operative tool for the definition of most suitable management actions for the protection and conservation of the archaeological heritage. In order to provide a first application of the proposed methodology, all coastal archaeological sites located in the Gulf of Naples (Southern Italy) have been investigated. The results are presented as a vulnerability map and highlight as seven archaeological sites present a high vulnerability level, four of which are located in two submerged archaeological parks (Underwater Archaeological parks of Baia and Gaiola). The other three sites (Terma Ginnasio, Pezzolo and Tiberio villas, 1st century BC) have no legal protection and therefore they require priority monitoring programs and preservation actions. Highlights: The vulnerability of archaeological sites to coastal processes was evaluated. Marine and aeolian processes acting in each coastal zone were considered. A set of vulnerability matrices was proposed for each coastal environment. A management strategy for the archaeological sites in the Gulf of Naples (Italy) was proposed.